An intensive combined training program modulates physical, physiological, biomotoric, and technical parameters in basketball player women - Klnc, F. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was the investigation of the effects of an intensive combined training program based on the pretest scores of a university women's basketball team on their physical, physiological, biomotoric, and technical features. Twenty-four university volunteers were equally divided into two groups: an experiment group (intensive combined training group) and a control (technical training) group. The 10-week intensive combined training program was performed on the experiment group according to their pretest outcomes. Before and at the end of each period of training, which was scheduled four times a week, the physical, physiological, biomotoric, and technical performance of each subject were determined. With respect to the pre- and posttest measurements, the basketball group showed significant differences (p < 0.05) in girth measurements (shoulder, waist, hip, arm, thigh, and calf), in skinfold measurements (percent body fat), in physiological measurements (vital capacity and forced vital capacity), in biomotoric tests (right-left hand grip, dynamic and countermovement jump, sit-up, push-up, 1500-m endurance), and in technique tests (free and inside shooting). It can be concluded that a 10-week intensive combined training program performed on university women basketball players had a significant effect on improving their physical, physiological, biomotoric, and technical features. It proved to be highly recommendable for female basketball players who are preparing for short-term tournaments; the basketball group in this study won a championship.